The Influence of Tax Planning on Firm Value in Food and Beverage Subsector Manufacturing Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2022 Period - Evelin, Ellena; Yuniawati, Ayi Srie; Krisdina, Tiana Fenny (SINTESA, 2024)
This research aims to determine the effect of tax planning on firm value in manufacturing sector companies in the food and beverage subsector on the Indonesia Stock Exchange. This analysis uses tax planning as the independent variable and firm value as the dependent variable. In this research, tax planning is measured by the Effective Tax Rate (ETR) and firm value is measured by the Price Earning Ratio (PER). The method used in this research is a quantitative method using secondary data from 28 companies. The research period was 5 years with sample data used of 140 research samples with a sampling technique using purposive sampling technique. The data analysis method used is simple linear regression analysis using SPSS version 25. The results of this research show that (1) tax planning has a negative and significant effect on company value as measured by Earning Per Share (EPS), (2) tax planning has an effect positive and significant on company value as measured by Earning Per Share (PER) (3) tax planning has no effect on company value as measured by Price Book Value (PBV).